Evaluation the correlations between childhood traumas and watching porn in adolescence - Aliyari, Farshad; Bakhtiari, Maryam; Kianimoghadam, Amir Sam (Researcher Bulletin of Medical Sciences, 2025)
Objective: Watching porn can have many consequences at different ages. Adolescence is one of these periods that is important for human sexual development, and unhealthy sexual development in this period may expose adolescents to a variety of problems such as high-risk sexual behaviors. Our aim in this study was to investigate the correlation between childhood traumas and watching porn in Iranian male adolescents. Materials and Methods: The research method of this study was cross-sectional and convenience sampling method was used for recruiting participants. 154 male adolescents completed the self-reported questionnaires through the online link. All analyses were performed by SPSS software version 26. Results: Results indicated that sexual abuse was significantly correlated with watching porn (rs = -0.161, p<0.05) and there weren’t any correlations between other traumas with it. Conclusion: Screening watching porn in adolescents at risk and incorporating prevention programs are needed. Future research that uses multiple methods of assessment, includes longitudinal designs, and identifies pathways between watching porn and adolescent health risks is recommended.